KONSEP IKHTILATH DALAM PERSPEKTIF AL-QUR’AN - Tharifatut Taulidia; Lizamah (JADID: Journal of Quranic Studies and Islamic Communication, 2023)
In the modern, various forms of association among human beings there’s been a lot deviation and across the boundaries of Islamic law for example ikhtila?h. Ikhtila?h is mixed up a boy and a girl who is not a mahram somewhere that allows both to look at each other even commit a heinous act. Ikhtila?h also interpreted as a form of free association which is forbidden by Islam. This paper will answer the question of how to interpret the ikhtila?h verses in the Al-Qur’an and how is the concept of ikhtila?h in the perspective Al-Qur’an. This paper comes to the conclusion that the results of this study indicate that there are 7 verses of the Qur’an related to ikhtila?h, including Q.S. Yûsuf [12]: 23, Q.S. al-Isr?’ [17]: 32, Q.S. an-Nûr [24]: 30 and 31, Q.S. al-Qhashâs [28]: 23 and 25, and Q.S. al-Ahzab [33]: 53. Ikhtila?h is male and female according to in perspective Al-Qur’an it’s not allowed. But, there is information that allows ikhtila?h if the perpetrator is accompanied by a mahram or someone he trusts, has a good purpose, and the atmosphere is safe from slander. Besides that, ikhtila?h also allowed in case of emergency like helping people in trouble, there is a need for sharia, and if you are in a celebration that has a positive value. Keywords: Al-Qur’an, Ikhtila?h, Thematic